ChemInform Abstract: Recent Advances in the Synthesis of Hierarchically Porous Silica Materials on the Basis of Porous Glasses. Issue 27 (16th June 2016) - Inayat, Alexandra; Reinhardt, Bjoern; Herwig, Jan; Kuester, Christian; Uhlig, Hans; Krenkel, Sharon; Raedlein, Edda; Enke, Dirk
Abstract: Review: 53 refs.